PENGEMBANGAN MEDIA ROLLING BALL GAME UNTUK MEMAHAMI MATERI PADA MATA PELAJARAN IPAS KELAS IV SEKOLAH DASAR - Sabikah, Sabikah; Marhamah, Marhamah; Ayurachmawati, Puji (STKIP Persada Khatulistiwa Sintang, 2024)
This study aims to produce a valid and practical rolling ball game media on the subject of Science for Grade IV Elementary School. The type of research used is Research & Development which apllied the ADDIE stage model with five stages, namely analysis, design, development, implementation, evaluation. The subjects of this study were grade IV students of Elementary School 21 Palembang. The validity test was obtained through a validation sheet by two (2) lecturers and one (1) teacher getting an average score of 81.4% with the category